The effect of a physical exercise program on functional capacity in patients with pulmonary arterial hypertension at Dr. M. Djamil Padang Hospital - Soegistiono, Feiky Herfandi; Krevani, Citra K.; Hamdani, Rita (The Indonesian Heart Association, 2025)
Background: Pulmonary arterial hypertension (PAH) has been known to cause a decreases functional capacity. The underlying mechanisms include right ventricular dysfunction, chronotropic incompetence, ventilation abnormalities, and skeletal muscle dysfunction. Although exercise training programs are recommended, there is currently no standardized exercise training program that is easy to implement in patients with PAH. We aimed to investigate the effect of exercise training program on functional capacity in patients with PAH. Methods: This study was a non-randomized clinical trial in adult patients with PAH who were divided into intervention and control groups. Cardiopulmonary exercise test (CPET) results were assessed before and after a four-week supervised program (5 sessions/week).The program followed the FITT principle: frequency 5 times/week, intensity 60–85% of six minute walk test (6MWT) distance, time 25–30 minutes/session including warm-up and cool-down, type supervised indoor walking. Shapiro-Wilk normality test was performed before analyzing the numerical data, followed by the independent t-test or Mann-Whitney U test to determine differences between groups. Results: This study included 26 patients with PAH, 14 in the intervention group, and 12 in the control group, consisting of 17 women (65%) and 9 men (35%) aged 18-54 years. Statistical analysis showed no significant differences in the baseline characteristics between the two groups (p >0.05). Characteristics of the CPET examination results before and after the exercise program. At baseline, there was no difference in VO2 peak in the intervention group and the control group (888.29 ± 435.99 (95% CI: 314-1823) vs 641.92 ± 231.98 (95% CI: 408 – 1111), p-value >0.05). After the physical exercise program, theintervention group showed a significant increase in VO2 peak (1047.71 ± 456.05 (95% CI: 413-2175) vs 656.5 ± 223.85 (95%CI: 401–1105), p-value < 0.05). Therefore, ΔVO2 peak in the intervention group was significantly higher (159.42 ± 209.32 (95%CI: -92 – 707) vs 14.5 ± 60.4 (95%CI: -77 – 148), p-value < 0.05) Conclusion: A four-week structured walking exercise program significantly improved functional capacity in PAH patients.